Reconstructing the full temporal range of archaeological phenomena from sparse data. (November 2021) - Key, Alastair; Roberts, David; Jarić, Ivan
Abstract: Archaeologists rarely discover the first or last known occurrences of past cultural phenomena, yet 'start' and 'end' dates are central to our understanding of past human behaviour; therein lays a paradox long known within the discipline. Optimal linear estimation (OLE) has recently been used to reconstruct the full temporal range of prehistoric archaeological technologies using only the partial records available. That is, OLE has been used to reconstruct the portions of the archaeological record not yet evidenced through artefact discoveries. Here we present OLE to a wider archaeological audience and outline for the first time the model's assumptions as they pertain to archaeological phenomena. We demonstrate OLE to be an accessible, user-friendly and methodologically transparent temporal range estimation method applied via a single set of equations. Further, we present five additional frequentist techniques that enable archaeologists to account for observation reliability, search effort and extreme data scarcity when inferring temporal ranges. These methods allow archaeologists to gain a more accurate understanding of the temporal range of past human behaviour. Highlights: Archaeologists rarely discover the first or last known occurrences of past cultural phenomena. OLE modelling is a method to reconstruct the full temporal range of archaeological phenomena using sparse data. OLE's assumptions are presented and discussed. We demonstrate OLE to be accessible and methodologically transparent, applicable to diverse archaeological fields.